The CK1 Family: Contribution to Cellular Stress Response and Its Role in Carcinogenesis - Knippschild, Uwe; Krüger, Marc; Richter, Julia; Xu, Pengfei; García-Reyes, Balbina; Peifer, Christian; Halekotte, Jakob; Bakulev, Vasiliy; Bischof, Joachim (Frontiers in Oncology, 2014)
Members of the highly conserved and ubiquitously expressed pleiotropic CK1 family play major regulatory roles in many cellular processes including DNA-processing and repair, proliferation, cytoskeleton dynamics, vesicular trafficking, apoptosis, and cell differentiation. As a consequence of cellular stress conditions, interaction of CK1 with the mitotic spindle is manifold increased pointing to regulatory functions at the mitotic checkpoint. Furthermore, CK1 is able to alter the activity of key regulatory proteins and signal integration molecules and is tightly connected to the regulation of β-catenin, p53- and MDM2-specific functions and degradation. Considering the importance of CK1 for accurate cell division and regulation of tumor suppressor functions it is not surprising that mutations and alterations in the expression and/or activity of CK1 isoforms are often detected in various tumor entities including cancer of the kidney, choriocarcinomas, breast carcinomas, oral cancer, adenocarcinomas of the pancreas, and ovarian cancer. Therefore, effort has enormously increased (i) to understand the regulation of CK1 and its involvement in tumorigenesis- and tumor progression-related signal transduction pathways and (ii) to develop CK1-specific inhibitors for the use in personalized therapy concepts. In this review we summarize the current knowledge regarding the regulation, functions, and interactions of CK1 family members with cellular proteins playing central roles in cellular stress-responses and carcinogenesis.